Mechanistic Studies on the Use of Polygonum multiflorum for the Treatment of Hair Graying. - Han, Ming-Nuan; Lu, Jian-Mei; Zhang, Guang-Yuan; Yu, Jie; Zhao, Rong-Hua (BioMed Research International, 2015)
Polygonum multiflorum is a traditional Chinese medicine with a long history in hair growth promotion and hair blackening. The purpose of the study was to examine the effect and the mechanism of Polygonum multiflorum in hair blackening. C57BL/6 mice hair fade was induced with H2O2 and used in this research. Hair pigmentogenesis promotion activities of Polygonum Multiflorum Radix (PMR, raw crude drug), Polygonum Multiflorum Radix Preparata (PMRP, processed crude drug), and their major chemical constituent TSG were investigated. The regulation effects of several cytokines and enzymes such as POMC, α-MSH, MC1R, ASIP, MITF, TYR, TRP-1, and TRP-2 were investigated. PMR group gave out the most outstanding black hair among all groups with the highest contents of total melanin, α-MSH, MC1R, and TYR. Promotion of hair pigmentogenesis was slightly decreased after processing in the PMRP group. TSG as the major constituent of PMR showed weaker hair color regulation effects than both PMR and PMRP. PMR, but not PMRP, should be used to blacken hair. The α-MSH, MC1R, and TYR were the major targets in the medicinal use of PMR in hair graying. Chemical constituents other than TSG may contribute to the hair color regulation activity of PMR.